Interhemispheric dynamics of the African rainbelt during the late Quaternary - Singarayer, J; Burrough, S (Elsevier, 2015)
The spatial pattern of precipitation variability in tropical and subtropical Africa over the late Quaternary has long been debated. Prevailing hypotheses variously infer (1) insolation-controlled asymmetry of wet phases between hemispheres, (2) symmetric contraction and expansion of the tropical rainbelt, and (3) independent control on moisture available in Southern Africa via sea surface temperatures in the Indian Ocean. In this study we use climate-model simulations covering the last glacial cycle (120 kyr) with HadCM3 and the multi-model ensembles from PMIP3 (the Palaeoclimate Model Intercomparison Project) to investigate the long-term behaviour of the African rainbelt, and test these simulations against existing empirical palaeohydrological records. Through regional model-data comparisons we find evidence for the validity of several hypotheses, with various proposed processes occurring concurrently but with different regional emphasis (e.g. asymmetric shifts at the seasonal extremes and symmetric expansions/contractions towards West equatorial regions). Crucially, variations in rainfall are associated with multiple forcing mechanisms that vary in their dominance both spatially and temporally over the glacial cycle; an important consideration when interpreting and extrapolating from often relatively short palaeoenvironmental records.